THE COMPLEXITY OF SOCIAL PATTERN ANALYSIS: A CASE STUDY OF AN AUTISTIC ADULT (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Autism Spectrum Disorder (ASD) is characterized by deficits in social interactions and communication and excessive repetitive behaviors and restricted interests. Studies suggest that adult people on the autism spectrum, not diagnosed in childhood, can develop classes of adaptive operants that mask socio-communicative difficulties, a phenomenon called camouflage. Behavior patterns can result in social inclusion and comorbidities, such as anxiety and depression. The objective of this article is to present a clinical case study and conceptual analysis of behaviors observed in the natural environment, related to ASD, using functional analysis, with principles of behavior analysis. A historical and situational analysis makes it possible to intervene in behavior patterns that result in suffering, with therapeutic goals of behavioral changes without negative individual and social impact. Using Behavioral Analytical Therapy, a clinical case of a young autistic woman showed the development of social behavior patterns, with reversal of comorbidities.
Keywords: Applied Behavior Analysis; Behavior Analysis; Autism